2016
DOI: 10.1021/acsami.6b03977
|View full text |Cite
|
Sign up to set email alerts
|

Injectable Hydrogel: Amplifying the pH Sensitivity of a Triblock Copolypeptide by Conjugating the N-Termini via Dynamic Covalent Bonding

Abstract: We explore the self-assembly behavior of aqueous solutions of an amphiphilic, pH-sensitive poly(l-alanine)-b-poly(l-glutamic acid)-b-poly(l-alanine), (A5E11A5) triblock copolypeptide, end-capped by benzaldehyde through Schiff base reaction. At elevated concentrations and under physiological pH (7.4) and ionic strength (0.15M), the bare copolypeptide aqueous solutions underwent a sol-gel transition after heating and slow cooling thermal treatment, forming opaque stiff gels due to a hierarchical self-assembly th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 68 publications
0
16
0
Order By: Relevance
“…The same concept of covalent reversible bonds can be used for the hydrogel formation and disruption. Examples of interactions used in this case are (Figure 2) electrostatic ones [19,20], cycloadditions [8,21], redox reactions [22,23,24], and other ones such as imine [25,26,27,28] and enamine formation [29], acylhydrazone [30,31,32,33], and borax acid reaction with hydroxyls [13,34,35,36].…”
Section: Dynamic Hydrogels Based On Reversible (Covalent) Interactmentioning
confidence: 99%
See 1 more Smart Citation
“…The same concept of covalent reversible bonds can be used for the hydrogel formation and disruption. Examples of interactions used in this case are (Figure 2) electrostatic ones [19,20], cycloadditions [8,21], redox reactions [22,23,24], and other ones such as imine [25,26,27,28] and enamine formation [29], acylhydrazone [30,31,32,33], and borax acid reaction with hydroxyls [13,34,35,36].…”
Section: Dynamic Hydrogels Based On Reversible (Covalent) Interactmentioning
confidence: 99%
“…Indeed, synthetic polymers are still widely used for the preparation of hydrogels, with polyacrylamide representing the most popular choice [45]. On the other hand, hydrogels based on natural products (e.g., chitosan [4,17], proteins [11,31,36], modified alginate [46], peptides [28,47]) represent a very convenient choice in view of clear advantages related to biological applications, but also to general sustainability principles. Indeed, attention is being paid also to novel synthetic pathways in agreement with green chemistry principles [48].…”
Section: Dynamic Hydrogels Based On Reversible (Covalent) Interactmentioning
confidence: 99%
“…For that purpose, pH-responsive polymeric systems are particularly appealing to selectively release therapeutics by exploiting the various pH gradients that exist in specific cellular compartments. The application of these polymers can further be expanded to other biological applications, including tumor-targeted delivery of drugs, intracellular delivery of nucleic acids or proteins, treatment of inflammatory diseases, and oral administration. , For example, imines, hydrazides, hydrazones, orthoesters, and acetal linkages degrade selectively in response to pH changes. , Among them, the imine linkage is of particular interest owing to its sensitivity under different acidic conditions, facilitating its widespread utility as a stimuli-responsive linkage. , As a notable example, Xu and co-workers conjugated doxorubicin to polymers through imine bond and demonstrated its pH-controlled drug release in acidic environments . In addition, Banerjee and co-workers developed pH-responsive glyconanoparticles conjugated to drugs through imine linkages …”
Section: Introductionmentioning
confidence: 99%
“…Among the various external stimuli, the pH/temperature responsiveness of hydrogels has been most extensively investigated in sensors and biological applications due to the controllability both under in vitro and in vivo conditions. [23][24][25] For example, Gao et al 26 reported a kind of sowood kra lignin pH-responsive hydrogels which were self-assembled through strong intermolecular hydrogen bonds in aqueous solution. However, most of them are formed from polymers.…”
Section: Introductionmentioning
confidence: 99%